A negative electrode material, preparation method and application thereof

By coating modified graphite materials with alumina/graphene composite materials, the problems of poor water dispersion and high production cost of negative electrode materials are solved, and high-performance and low-cost lithium-ion battery negative electrode materials are achieved.

CN116002679BActive Publication Date: 2025-01-21コーネックス ニュー エナジー カンパニー リミテッド
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310144986.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-01-21
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials have poor water dispersion, are prone to precipitation when left to stand, and the spray drying equipment is high and the thermal efficiency utilization rate is low, resulting in high cost of large-scale production.

Method used

The graphite material is coated and modified with alumina/graphene composite material, and the composite material is evenly coated on the surface of the graphite material to improve the conductivity and compatibility, and the negative electrode material is prepared through ball milling and calcination.

Benefits of technology

It improves the water solubility and standing stability of the lithium-ion battery negative electrode material, improves the battery's cycle performance, rate performance and safety performance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116002679B_ABST
    Figure CN116002679B_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode material, a preparation method and an application thereof; the negative electrode material comprises a graphite material coated and modified by an aluminum oxide / graphene composite material, wherein the aluminum oxide and the graphene are uniformly coated on the surface of the graphite material by forming a composite material. The present invention can improve the conductivity of the negative electrode material and the rate performance by coating and modifying the graphene; and can improve the compatibility of the negative electrode material with the electrolyte by coating and modifying the aluminum oxide, utilizing its good stability, inhibiting the decomposition of the electrolyte, and improving the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new electrochemical materials, and in particular relates to a negative electrode material, a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have advantages such as high operating voltage and high energy density, making them widely used in mobile phones, laptops, electric vehicles, etc. At present, the negative electrode materials of lithium-ion batteries mainly include natural graphite, artificial graphite, lithium titanate, Si materials, Sn materials and other alloy materials. Among them, graphite is widely used due to its high lithium insertion capacity, stable discharge platform, easy processing, rich resources and low price; however, graphite has poor compatibility with electrolyte, resulting in poor electrolyte immersion, causing solvents to co-embed and peel off the graphite layer, which in turn leads to unstable SEI film, electrolyte decomposition, and poor battery cycle performance.

[0003] Graphene is carbon atoms in the form of SP 2 The single atomic layer two-dimensional crystal formed by hybrid connection has the characteristics of high strength, high thermal conductivity, extremely high electron current carrying rate, high electrical conductivity, etc. It has excellent application prospects in different fields. Graphene can be used to coat and modify graphite to improve the conductivity of graphite and enhance the rate performance. Invention patent CN113955747A discloses a method for preparing a graphene-coated natural graphite negative electrode material, which uses graphene as a coating agent and natural graphite as a raw material to prepare a high-performance lithium-ion battery negative electrode material by spray drying; first, the graphene powder and the solvent are prepared into a dispersion liquid in a certain proportion, and then mixed with natural graphite in a certain proportion, and finally, the graphene-coated natural graphite negative electrode material is obtained by controlling the spray drying parameters; however, the obtained negative electrode material has poor dispersibility in water, is easy to precipitate after standing for a long time, and the investment cost of the spray drying equipment is large, the thermal efficiency utilization rate is low, and the large-scale production cost is high. Summary of the invention

[0004] In view of the shortcomings and defects of the prior art, the present invention aims to provide a negative electrode material, a preparation method and its application, using an aluminum oxide / graphene composite material as a coating agent to coat and modify a graphite material so that the aluminum oxide / graphene composite material can be evenly dispersed on the graphite surface, and the graphene coating modification can improve the conductivity of the negative electrode material and improve the rate performance; by coating and modifying the aluminum oxide, the good stability of the aluminum oxide can be used to improve the compatibility of the negative electrode material with the electrolyte, inhibit the decomposition of the electrolyte, and improve the cycle performance of the battery; the present invention first dissolves the aluminum oxide in a strong alkali A metaaluminate solution is obtained from the solution, and the characteristic of metaaluminate being soluble in water is utilized to suspend graphene oxide in the metaaluminate solution through ultrasonic dispersion, and then a weak acid reaction is used to obtain an aluminum hydroxide / graphene oxide suspension with an ultrafine structure, and the aluminum oxide / graphene oxide composite material powder is obtained through aging and baking treatment, and finally the aluminum oxide / graphene oxide composite material powder is subjected to ball milling treatment and calcination treatment with a graphite material to obtain a negative electrode material. The lithium ion battery negative electrode material obtained by the preparation method of the invention has good hydrophilicity and is convenient for stirring and coating, and has good negative electrode interface, cycle performance, rate performance and safety performance when preparing a finished battery cell.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a negative electrode material, which adopts the following technical solution:

[0006] A negative electrode material comprises a graphite material modified by coating an aluminum oxide / graphene composite material, wherein the aluminum oxide and the graphene are uniformly coated on the surface of the graphite material by forming a composite material.

[0007] In the above-mentioned negative electrode materials, as a preferred embodiment, the aluminum oxide / graphene composite material is obtained by dispersing graphene oxide in an aluminate solution, subjecting the obtained aluminum oxide / graphene oxide composite material to a weak acid reaction and aging and baking treatment, and then calcining the obtained aluminum oxide / graphene composite material in a protective gas.

[0008] In the above-mentioned negative electrode materials, as a preferred embodiment, the graphite material is selected from one or more of natural graphite, artificial graphite, and graphite materials treated by other methods.

[0009] A second aspect of the present invention provides a method for preparing the above-mentioned negative electrode material, comprising:

[0010] (1) adding aluminum oxide to a strong alkaline solution for dispersion treatment, and then filtering to remove insoluble matter to obtain a metaaluminate solution;

[0011] (2) adding graphene oxide to the aluminate solution of step (1), and then performing ultrasonic dispersion treatment to obtain a graphene oxide / aluminate suspension;

[0012] (3) adding a weak acid solution dropwise to the graphene oxide / aluminate suspension of step (2) and stirring, stopping the addition of the weak acid solution when the pH value of the system is 5-7, and then heating to obtain a gel;

[0013] (4) subjecting the gel of step (3) to an aging and baking treatment to obtain an aluminum oxide / graphene oxide composite material powder;

[0014] (5) adding the aluminum oxide / graphene oxide composite material powder of step (4) into the graphite material for ball milling, and then calcining in a protective gas to obtain a negative electrode material.

[0015] The present invention first prepares a graphene oxide / aluminate suspension, then drips a weak acid to obtain ultrafine particles of Al(OH)3, the graphene oxide is uniformly attached to the Al(OH)3 particles, and an aluminum oxide / graphene oxide composite material powder is obtained after aging and baking, and then the aluminum oxide / graphene oxide composite material is subjected to ball milling and calcination to obtain a graphite material coated with the aluminum oxide / graphene composite material, i.e., a negative electrode material; wherein the chemical reaction involved in step (1) is: Al2O3+2OH - →2AlO2 - +H2O; the chemical reaction involved in step (3) is: AlO2 - +H + +H2O→Al(OH)3; the chemical reaction involved in step (4) is: 2Al(OH)3→Al2O3+3H2O; through step (5), the aluminum oxide / graphene oxide composite material is calcined at a certain temperature in an inert atmosphere by a solid phase thermal reduction method, and the functional groups on the surface of the graphene oxide are decomposed to release CO2 and H2O to expand the interlayer spacing, thereby achieving the purpose of reducing the graphene oxide and peeling it into a single layer of graphene, thereby obtaining a graphite material coated with the aluminum oxide / graphene composite material. The preparation method of the present invention has a simple process, common equipment, is easy to obtain, and is easy to promote.

[0016] In the above preparation method, as a preferred embodiment, in step (1), the alkaline solute in the strong alkaline solution is at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide;

[0017] Preferably, the molar ratio of the aluminum oxide to the alkaline solute is 1:1-4 (e.g., 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5);

[0018] Preferably, the dispersion treatment is magnetic suspension stirring, and the magnetic suspension stirring time is 0.5-2h (such as 0.8h, 1h, 1.2h, 1.5h, 1.8h);

[0019] Preferably, the number of filtering processes is ≥1.

[0020] In the above preparation method, as a preferred embodiment, in step (2), the mass ratio of the graphene oxide to the aluminum oxide in step (1) is 1:10-50 (e.g., 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45);

[0021] Preferably, the ultrasonic dispersion treatment time is 2-10 h (such as 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h).

[0022] In the above preparation method, as a preferred embodiment, in step (3), the acidic solute in the weak acid solution is at least one of formic acid, acetic acid, and carbonic acid;

[0023] Preferably, in the weak acid solution, the molar concentration of the acidic solute is 0.01-1 mol / L (e.g., 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.5 mol / L, 0.7 mol / L, 0.9 mol / L);

[0024] Preferably, the droplet acceleration rate of the weak acid solution is 1-5 mL / min (such as 1.5 mL / min, 2 mL / min, 2.5 mL / min, 3 mL / min, 3.5 mL / min, 4 mL / min, 4.5 mL / min);

[0025] Preferably, the temperature of the heating treatment is 50-90°C (such as 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C).

[0026] In the above preparation method, as a preferred embodiment, in step (4), the temperature of the aging baking treatment is 160-250°C (for example, 170°C, 180°C, 200°C, 210°C, 230°C, 240°C), and the time is 1-3h (for example, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h).

[0027] In the above preparation method, as a preferred embodiment, in step (5), the mass ratio of the graphite material to the aluminum oxide / graphene oxide composite material powder is 100:0.5-2 (such as 100:0.6, 100:0.8, 100:1, 100:1.2, 100:1.5, 100:1.8);

[0028] Preferably, the calcination treatment is carried out at a heating rate of 3-5°C / min (e.g., 3.2°C / min, 3.5°C / min, 4°C / min, 4.2°C / min, 4.5°C / min, 4.8°C / min) to 800-1500°C (e.g., 850°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C), and kept at this temperature for 7-13h (e.g., 7.5h, 8h, 9h, 10h, 11h, 12h, 12.5h);

[0029] Preferably, the protective gas is nitrogen or argon.

[0030] A third aspect of the present invention provides an application of the above-mentioned negative electrode material or the negative electrode material prepared by the above-mentioned preparation method in a lithium-ion battery.

[0031] Compared with the prior art, the advantages of the present invention are:

[0032] (1) The lithium-ion battery negative electrode material prepared by the present invention has good water solubility and does not precipitate when left standing for a long time, thereby improving the problem of unstable surface density and abnormal battery cell interface caused by precipitation during coating, solving the problem of abnormal cracks that are prone to occur when NMP is not used in the stirring process, and reducing pollution.

[0033] (2) The lithium-ion battery negative electrode material prepared by the present invention has good immersion performance in the electrolyte, the SEI film on the negative electrode surface is stable, and it has a high initial efficiency and can inhibit the decomposition of the electrolyte. The battery cell prepared has good cycle performance, rate performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The present invention is a flow chart for preparing negative electrode materials.

[0035] Figure 2 This is a SEM image of the negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0037] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0038] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0039] In the present invention, unless otherwise specified and / or described, all numerical values ​​involving the amount of components are "parts by weight" from beginning to end. The process parameters of the following examples without specifying specific conditions are usually based on conventional conditions. The raw materials described in the following examples can all be obtained from public commercial channels, wherein the graphite material refers to natural graphite, which is purchased.

[0040] The present invention will be further described in detail below with reference to specific embodiments.

[0041] Embodiment 1 A method for preparing a negative electrode material comprises:

[0042] (1) adding 10.2 g of aluminum oxide to 1000 mL of a strong alkaline solution, performing a magnetic suspension stirring treatment for 1 h, and then performing a filtration treatment twice to remove insoluble matter to obtain an aluminate solution; wherein the alkaline solutes in the strong alkaline solution are lithium hydroxide and sodium hydroxide, and the molar concentration of lithium hydroxide and sodium hydroxide is 0.1 mol / L;

[0043] (2) adding 0.52 g of graphene oxide to the aluminate solution of step (1), followed by ultrasonic dispersion treatment for 5 h to obtain a graphene oxide / aluminate suspension;

[0044] (3) adding 0.1 mol / L acetic acid solution to the graphene oxide / aluminate suspension of step (2) at a dropping speed of 2.5 mL / min and stirring, stopping the addition of acetic acid solution when the pH value of the system reaches 5, and then heating to 80° C. and evaporating to obtain a gel;

[0045] (4) subjecting the gel of step (3) to an aging and baking treatment to obtain an aluminum oxide / graphene oxide composite material powder; wherein the aging and baking treatment is performed at a temperature of 220° C. for 1 h;

[0046] (5) 1 g of the aluminum oxide / graphene oxide composite material powder of step (4) was added to 120 g of graphite material for ball milling for 4 h, and then the temperature was increased to 1200 ° C at a heating rate of 5 ° C / min under a nitrogen atmosphere, and kept warm for 8 h to obtain a lithium ion battery negative electrode material.

[0047] Example 2

[0048] The difference between Example 2 and Example 1 is that 0.6 g of aluminum oxide / graphene oxide composite material powder is added in step (5), and the rest is the same as Example 1.

[0049] Example 3

[0050] The difference between Example 3 and Example 1 is that 2.4 g of aluminum oxide / graphene oxide composite material powder is added in step (5), and the rest is the same as Example 1.

[0051] Example 4

[0052] The difference between Example 4 and Example 1 is that 0.204 g of graphene oxide is added in step (2), and the rest is the same as Example 1.

[0053] Example 5

[0054] The difference between Example 5 and Example 1 is that 1.02 g of graphene oxide is added in step (2), and the rest is the same as Example 1.

[0055] Comparative Example 1

[0056] The negative electrode material in Comparative Example 1 is the untreated graphite material used in step (5) of Example 1.

[0057] Comparative Example 2 A method for preparing a negative electrode material comprises:

[0058] 1 g of graphene oxide powder was added to 120 g of graphite material and ball-milled for 4 h. The temperature was then raised to 1200° C. at a heating rate of 5° C. / min under a nitrogen atmosphere and kept at this temperature for 8 h to obtain a negative electrode material.

[0059] Comparative Example 3 A method for preparing a negative electrode material comprises:

[0060] 1 g of alumina powder was added to 120 g of graphite material and ball-milled for 4 h to obtain a negative electrode material.

[0061] Comparative Example 4

[0062] The difference between Comparative Example 4 and Example 1 is that 0.5 g of aluminum oxide / graphene oxide composite material powder is added in step (5), and the rest is the same as Example 1.

[0063] Comparative Example 5

[0064] The difference between Comparative Example 5 and Example 1 is that 3 g of aluminum oxide / graphene oxide composite material powder is added in step (5), and the rest is the same as Example 1.

[0065] Performance Testing

[0066] The materials prepared in Examples 1-5 and Comparative Examples 1-5 were used as active materials, mixed with CMC, conductive carbon black Super P, and binder SBR in a mass ratio of 96:1:1.2:1.8, and then ground in an agate grinding mortar for 30 minutes, and deionized water was added to continue grinding the mixture until it was in a paste state; the slurry was then coated on a metal copper foil and dried in a vacuum at 60°C for 12 hours, and finally cut into circular electrodes with a diameter of 12 mm using a punch as working electrodes; in a purified glove box filled with Ar (O2 content less than 0.1 ppm, H2O content less than 0.1 ppm), metallic lithium was used as the counter electrode, Celgard 2400 porous polypropylene film (PP) is used as the separator, the electrolyte is 1 mol / L lithium hexafluorophosphate (LiPF6) solution, and the solvent is a mixed solution of ethylene carbonate (EC): ethyl carbonate (DMC): ethyl methyl carbonate (EMC) = 1:1:1 volume ratio. The CR2032 button battery is prepared according to a certain assembly process. After completion, it is left to stand for 24 hours to allow the electrolyte and electrode materials to fully infiltrate. At room temperature (25℃±1), it is charged to 2.0V at 0.1C and discharged to 0.005V at 0.1C. The Li / Li + Constant current charge and discharge experiments and cycle performance experiments were carried out; the test results are shown in Table 1.

[0067] Table 1

[0068]

[0069]

[0070] It can be seen from Examples 1-5 and Comparative Examples 1-5 in Table 1 that the use of alumina / graphene composite materials to coat and modify graphite materials can improve the initial coulombic efficiency and cycle performance of the battery. This is because the prepared alumina / graphene composite materials can be evenly coated on the surface of the graphite material, giving it good hydrophilicity and conductivity, and can be left to stand for a long time without precipitation, thereby improving the stability of the surface density of the negative electrode sheet in the coating process, and at the same time improving the immersion performance of the negative electrode material and the electrolyte, which is conducive to the formation of a more stable SEI film on the negative electrode surface.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises a graphite material modified by coating an aluminum oxide / graphene composite material, wherein the aluminum oxide and the graphene are uniformly coated on the surface of the graphite material by forming a composite material; The negative electrode material is prepared according to the following steps: (1) Alumina is added to a strong alkaline solution for dispersion treatment, and then filtered to remove insoluble matter to obtain a metaaluminate solution; (2) adding graphene oxide to the aluminate solution of step (1), and then performing ultrasonic dispersion treatment to obtain a graphene oxide / aluminate suspension; (3) adding a weak acid solution dropwise to the graphene oxide / aluminate suspension of step (2) and stirring, stopping the addition of the weak acid solution when the pH value of the system is 5-7, and then heating to obtain a gel; (4) subjecting the gel of step (3) to aging and baking treatment to obtain aluminum oxide / graphene oxide composite material powder; (5) adding the aluminum oxide / graphene oxide composite material powder of step (4) to graphite material for ball milling treatment, and then calcining in a protective gas to obtain a negative electrode material; In step (5), the mass ratio of the graphite material to the aluminum oxide / graphene oxide composite material powder is 100:0.5-2.

2. The negative electrode material according to claim 1, characterized in that The graphite material is selected from one or more of natural graphite and artificial graphite.

3. A method for preparing a negative electrode material as claimed in any one of claims 1 to 2, characterized in that: include: (1) Alumina is added to a strong alkaline solution for dispersion treatment, and then filtered to remove insoluble matter to obtain a metaaluminate solution; (2) adding graphene oxide to the aluminate solution of step (1), and then performing ultrasonic dispersion treatment to obtain a graphene oxide / aluminate suspension; (3) adding a weak acid solution dropwise to the graphene oxide / aluminate suspension of step (2) and stirring, stopping the addition of the weak acid solution when the pH value of the system is 5-7, and then heating to obtain a gel; (4) The gel of step (3) is aged and baked to obtain an aluminum oxide / graphene oxide composite material powder; (5) The aluminum oxide / graphene oxide composite material powder of step (4) is added to a graphite material for ball milling, and then calcined in a protective gas to obtain a negative electrode material.

4. The preparation method according to claim 3, characterized in that: In step (1), the alkaline solute in the strong alkaline solution is at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide; and / or, the molar ratio of the aluminum oxide to the alkaline solute is 1:1-4; And / or, the dispersion treatment is magnetic suspension stirring, and the magnetic suspension stirring time is 0.5-2h; And / or, the number of filtering processes is ≥1.

5. The preparation method according to claim 3, characterized in that: In step (2), the mass ratio of the graphene oxide to the aluminum oxide in step (1) is 1:10-50; And / or, the ultrasonic dispersion treatment time is 2-10 hours.

6. The preparation method according to claim 3, characterized in that: In step (3), the acidic solute in the weak acid solution is at least one of formic acid, acetic acid, and carbonic acid; And / or, in the weak acid solution, the molar concentration of the acidic solute is 0.01-1 mol / L; and / or, the dropping rate of the weak acid solution is 1-5 mL / min; And / or, the temperature of the heating treatment is 50-90°C.

7. The preparation method according to claim 3, characterized in that: In step (4), the aging baking treatment is performed at a temperature of 160-250° C. and for a time of 1-3 hours.

8. The preparation method according to claim 3, characterized in that: In step (5), the calcination treatment is to increase the temperature to 800-1500°C at a heating rate of 3-5°C / min and keep the temperature for 7-13h; And / or, the protective gas is nitrogen or argon.

9. Use of the negative electrode material according to any one of claims 1 to 2 or the negative electrode material prepared by the preparation method according to any one of claims 3 to 8 in a lithium ion battery.

Citation Information

Patent Citations

  • Preparation method of graphene-coated natural graphite negative electrode material

    CN113955747A

  • Preparation method of graphene / alumina co-clad anode material for lithium-ion battery

    CN106410151A

  • Graphite negative electrode composite material, preparation method thereof and lithium ion battery

    CN115207304A